Implementation of Pyrolysis Tools for Green Innovation in TPST Dewanata, Dieng Kulon - Ashar, Haris Nur; Abdullah, Faqih Nur (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
This article analyzes the role of Corporate Social Responsibility (CSR) in driving green innovation in the Dieng Plateau Region through the use of pyrolysis tools at TPST Dewanata (Dieng Waste Management and Treatment) in Dieng Kulon. Generally, the Dieng area is a major tourist destination in Central Java Province. This situation leads to waste-related problems. Waste management in Dieng faces unique challenges, particularly due to its geographical conditions, the increasing number of tourists, and limited land. These waste issues are the responsibility of all community elements, including the government, community groups, and existing companies. Through CSR programs, companies actively provide solutions to existing community problems, especially environmental issues like waste. PT Geo Dipa Energi, as one of the companies in Dieng, plays an active role in the TPST Dewanata program in Dieng Kulon through its CSR initiatives. This article discusses how the CSR program promotes sustainable waste management by implementing pyrolysis tools at TPST Dewanata. The researchers used a qualitative research method to describe and analyze the role of CSR in bringing green innovation to Dieng. Specifically, it outlines the process of designing the pyrolysis tool, its operation, and the impact of reducing plastic waste produced. The research results indicate that the implementation of the pyrolysis tool at TPST Dewanata is an environmentally friendly technological solution that can also save TPST Dewanata's operational costs.